DAYA GUNA SISTEM RESERVASI ONLINE MELALUI WEBSITE DALAM MENINGKATKAN MINAT BELI ULANG TIKET PADA PENUMPANG MASKAPAI CITILINK - Puspitasari, Yulia Aji (Juremi: Jurnal Riset Ekonomi, 2025)
The rapid advancement of technology has extended to all aspects of life, including ticket reservations, which are now widely available online through e-commerce platforms and official websites. Citilink, as an airline, must continuously consider and develop its online ticket reservation services through its website to remain competitive against numerous competitors. The purpose of this research is to understand the usability of the online reservation system on Citilink's official platform in increasing passenger ticket repurchase intention and to identify the obstacles that influence passengers' willingness to repurchase tickets through Citilink's online reservation system. This study employs a descriptive qualitative research method. Data collection was conducted through interviews and documentation. The data analysis process included data reduction, data presentation, and drawing conclusions. Based on the findings, it can be concluded that Citilink's online reservation system has significant potential to increase passenger repurchase intention. This potential is supported by features that enhance ease of use, service speed, and the availability of accurate information. However, several obstacles affect repurchase intention, including system disruptions, less competitive pricing, and the lack of effective socialization or promotion efforts by Citilink